2011
DOI: 10.1177/1470320311430989
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms of angiotensin-converting enzyme and angiotensin II Type 1 receptor among chronic kidney disease patients in a Chinese population

Abstract: Chronic kidney disease (CKD) is highly prevalent in Taiwan and an increasing number of patients are affected, with a high risk of progression to end-stage renal disease and huge medical expenses. It has been predicted that the presence of hypertension increases with decreasing renal function due to a decrease in sodium excretion and activation of the renin-angiotensin system (RAS). The aim of this study was to investigate the influence of genetic variants of the RAS gene on CKD. We performed a case control ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The SNP has been investigated to have an association with hypertension in Pakistani and Gulf populations [32,33]. In addition, significant association of A2350G was also observed with chronic kidney disease (CKD) in Taiwanese and SLE in Northern Chinese Han [10,34]. The findings indicated the SNP could be served as the regulator to the blood pressure, and thus leading to the renal complications, such as diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 85%
“…The SNP has been investigated to have an association with hypertension in Pakistani and Gulf populations [32,33]. In addition, significant association of A2350G was also observed with chronic kidney disease (CKD) in Taiwanese and SLE in Northern Chinese Han [10,34]. The findings indicated the SNP could be served as the regulator to the blood pressure, and thus leading to the renal complications, such as diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 85%
“…In a study by Su et al , 6 135 CKD patients and 270 healthy controls among Han Chinese in Taiwan were genotyped for angiotensinogen (AGT-M235T, T174M, A-20C), angiotensin-I-converting enzyme (ACE-A2350G), and angiotensin II type 1 receptor (AGTR1-A1166C, C573T, C-521T) polymorphisms by polymerase chain reaction-restriction fragment length polymorphism analysis. Significant associations were observed in ACE-A2350G and AGTR1-C573T polymorphism in CKD patients ( P =0.01 and P =0.03, respectively).…”
Section: Genetic Componentmentioning
confidence: 99%
“…In patients with CKD, risk factors for hypertension include the renin-angiotensin system, endothelin, stimulating peptide, nitric oxide, and vasoactive substances such as renal enzyme factors. Several studies have shown that SNPs in genes related to these factors may influence the development of CKD [19][20][21][22][23] and hypertension in patients with CKD [24,25].…”
Section: Introductionmentioning
confidence: 99%